Non-Tension Hernioplasty for Pinched Ventral Hernia (Eurasian Medical Research Periodical, 2023)
The main causes of anterior abdominal wall suture inconsistency and hernia recurrence are excessive traumatization of the wound defect margins with their excessive forced rapprochement, insufficient adaptation of the tissues under stitching and increased intraabdominal pressure that leads to high diaphragm position and decreased lung excursion, hypoventilation and hypoxia, which in its turn aggravates bowel paralysis and progressive increase of intra-abdominal pressure